Clarificação de vinho branco por microfiltração utilizando diferentes membranas cerâmicas e compósitas - Cristofoli, Kélen (My University, 2017)
The tangential microfiltration applied to the clarification of white wine has become an important alternative to conventional filtration processes in the wine industry, for example, the filtration diatomaceous earth, land transfer and centrifugation. The use of ceramic membranes has awakened interest for this purpose. In this work, different and tubular composite ceramic membranes, mono and multi-channel, of different sizes of pore, were evaluated for their morphology and hydraulic permeability tests and white wine, in order to verify the influence of the structure of these in white wine flow permeated as well, evaluate the presence of suspended solids in the waste wine due to its process of clarification. The membranes were characterized by x-ray diffraction (XRD), scanning electron microscopy by field emission (FESEM), energy dispersive spectroscopy (EDS), porosimetria by mercury intrusion tests, permeability and protein retention. The average pore size presented by membranes ranged from 0.0056 to 5.0 µm. Composite membranes showed great protein retention, 99%, for solutes with molecular weight up to 45 kDa. α-alumina membranes treated thermally to 1450ºC and composite membranes of α-alumina/polyamide 66 showed, on average, 99.9% reduction of wine’s turbidity, being possible to reduce from 720 NTU to average 0.30 NTU, with possibility of tartaric stabilization in seven days and permeate fluxes that ranged from 60.8 to 8.8 L. m-2h-1, respectively, the 1.0 bar pressure. On the other hand, mullite and titania membranes have not shown effectiveness for clarification, the wine permeated by the membrane of mullite presented turbidity of 20 NTU and increase the rate of total polyphenols (IPT). Composite membranes have enabled the reduction of 37% in the value of IPT of the white wine. The low turbidity value obtained in wine permeated by composite and alumina membranes, strong perspective of use demonstrates of these membranes in the clarification of white wine.
A microfiltração tangencial aplicada à clarificação de vinho branco tem se tornado uma importante alternativa aos processos convencionais de filtração na indústria vinícola, como a filtração por terras diatomáceas, trasfega e centrifugação. O uso de membranas cerâmicas tem despertado interesse para esta finalidade. Neste trabalho, diferentes membranas cerâmicas e compósitas tubulares, mono e multicanal, de diferentes tamanhos de poro, foram avaliadas quanto à sua morfologia e testes de permeabilidade hidráulica e do vinho branco, a fim de verificar a influência da estrutura destas no fluxo de vinho branco permeado, bem como, avaliar a presença de resíduos sólidos suspensos no vinho permeado decorrente de seu processo de clarificação. As membranas foram caracterizadas por difração de raios X (DRX), microscopia eletrônica de varredura por emissão de campo (FESEM), espectroscopia de dispersão de energia (EDS), porosimetria por intrusão de mercúrio, testes de permeabilidade e retenção de proteínas. O tamanho médio de poro apresentado pelas membranas variou de 0,0056 a 5,0 µm. As membranas compósitas apresentaram ótima retenção proteica, 99%, para solutos com massa molar acima de 45 kDa. Membranas de α-alumina tratadas termicamente a 1450ºC e membranas compósitas de α-alumina/poliamida 66 demonstraram, em média, redução de 99,9% da turbidez inicial do vinho, sendo possível reduzir de 720 NTU para, em média, 0,30 NTU, com possibilidade de estabilização tartárica em sete dias e fluxos de permeado que variaram de 60,8 a 8,8 L.m-2.h-1, respectivamente, a 1,0 bar de pressão. Por outro lado, membranas de mulita e titânia não demonstraram eficiência para a clarificação, sendo que o vinho permeado pela membrana de mulita apresentou turbidez de 20 NTU e aumento do índice de polifenóis totais (IPT). Membranas compósitas permitiram a redução de 37% no valor de IPT do vinho branco. O baixo valor de turbidez obtido nos vinhos permeados pelas membranas de alumina e compósitas demonstra forte perspectiva da utilização destas membranas na clarificação do vinho branco.
Keywords: Vinho branco; Permeabilidade; Membranas (Tecnologia); Vinho e vinificação; White vine; Permeability; Membranes (Technology); Wine and wine making